High frequency oscillatory ventilation in leptospirosis pulmonary haemorrhage: A case series - Mat Nor, Mohd Basri; Md Ralib, Azrina; Ibrahim, Nor Airini; Abdul Ghani, Muhamad Rasydan (Indian Society of Critical Care Medicine, 2016)
Hypoxemia in severe leptospirosis-associated pulmonary hemorrhage syndrome (LPHS) is a challenging clinical scenario not usually responsive to maximal support on mechanical ventilation. We described the efficacy and safety of high frequency oscillatory ventilation (HFOV) as rescue therapy in acute respiratory failure secondary to LPHS. This is a retrospective case study of five patients with diagnosis of severe LPHS, who were admitted to Intensive Care Unit from October 2014 to January 2015. They developed refractory hypoxemia on conventional mechanical ventilation and rescue therapy was indicated. All patients responded rapidly by showing improvements in oxygen index and PaO2/FiO2 ratio within first 72 h of therapy. Despite severity of illness evidenced by high Simplified Acute Physiological II and Sequential Organ Failure Assessment scores, all patients were discharged from hospital alive. In view of the rapid onset and extent of hemorrhage which may culminate quickly into asphyxiation and death, HFOV may indeed be lifesaving in severe LPHS.